Efektifitas Deep Back Massage Dan Effleurage Massage Terhadap Penurunan Intensitas Nyeri Persalinan Kala I Fase Aktif Pada Ibu Primipara Di Puskesmas Jumpandang Baru Makassar - Rosita Rosita; Maria Yasintha Lowa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objecvtive : The pain felt during the delivery is a problem which is woring the delivery mothers. various attempts are used to reduce the pain caused bt delivery ; nevertheless there is a method which can be utilized and those are the deep back massage and the effelurage massage. This research aimed to compare which massage is more effective between deep back or effleurage massage. Methods: The research design was quantitative research by using a quasy experimental design, two groups pre test and post test design. Results: The results of the bivariate analysis of the Wilcoxon Test in the deep back massage treatment group obtained p-value 0.0001, while in the treatment group effleurage massage the results of p-value is 0.0001. The Mann-Whitney test results obtained p-value 0.006. Conclusion: The conclusion of this study shows that there is a comparison between the effectiveness of deep back massage with effleurage massage to reduce the intensity of labor pain in the active phase of the first phase of primipara women in the Jumpandang Baru Health Center Makassar.